Pilot-WINGS: An extended MUSE view of the structure of Abell 370. Issue 1 (1st June 2022) - Lagattuta, David J; Richard, Johan; Bauer, Franz Erik; Cerny, Catherine; Claeyssens, Adélaïde; Guaita, Lucia; Jauzac, Mathilde; Jeanneau, Alexandre; Koekemoer, Anton M; Mahler, Guillaume; Prieto Lyon, Gonzalo; Acebron, Ana; et al.
ABSTRACT: We investigate the strong-lensing cluster Abell 370 (A370) using a wide Integral Field Unit (IFU) spectroscopic mosaic from the Multi-Unit Spectroscopic Explorer (MUSE). IFU spectroscopy provides significant insight into the structure and mass content of galaxy clusters, yet IFU-based cluster studies focus almost exclusively on the central Einstein-radius region. Covering over 14 arcmin 2, the new MUSE mosaic extends significantly beyond the A370 Einstein radius, providing, for the first time, a detailed look at the cluster outskirts. Combining these data with wide-field, multi-band Hubble Space Telescope ( HST ) imaging from the BUFFALO project, we analyse the distribution of objects within the cluster and along the line of sight. Identifying 416 cluster galaxies, we use kinematics to trace the radial mass profile of the halo, providing a mass estimate independent from the lens model. We also measure radially averaged properties of the cluster members, tracking their evolution as a function of infall. Thanks to the high spatial resolution of our data, we identify six cluster members acting as galaxy–galaxy lenses, which constrain localized mass distributions beyond the Einstein radius. Finally, taking advantage of MUSE's 3D capabilities, we detect and analyse multiple spatially extended overdensities outside of the cluster that influence lensing-derived halo mass estimates. We stress that much of this work is only possible thanks to the robust, extended IFU coverage, highlighting its importance even in less optically dense cluster regions. Overall, this work showcases the power of combining HST + MUSE, and serves as the initial step towards a larger and wider program targeting several clusters.